RECENT RECORD OF DESERT YELLOW HOUSE BAT, SCOTOECUS PALLIDUS (ORDER CHIROPTERA) FROM PUNJAB, PAKISTAN - M. Shahbaz; A. Javid; S. M. Hussain; M. Ashraf; H. Azmat (Journal of Animal and Plant Sciences, 2015)
The desert yellow house bat, Scotoecus pallidus is an endemic species of Indian sub-continent with type locality Mian Mir, Lahore, During present study 36 specimens of S. pallidus were captured from Gujranwala, Mandi Bhauddin and Hafizabad districts of Punjab, Pakistan The morphological features, external body, cranial and bacular measurements of captured specimens were compared with available literature. Average head and body length of all the captured specimens (n = 36) of S. pallidus was 55.9 mm, average forearm length was 37.0 mm, greatest skull length (n = 5) was 14.8 mm while average baculum length (n = 3) was 5.0 mm. Bacular features of the species are reported for the first time in country.
Keywords: Cranial measurements; baculum size; agro-ecosystem; Punjab